Microbial quality of razor clams (solen spp.) sold by vendors in the Kuching Samarahan division - Sarah Hanisah, bt Mohd Zaifullizan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Seafood-borne diseases have been increasingly recognized as a threat to human health. This is due to pathogenic bacteria that are present in the tissues of these seafood. The accumulation of pathogenic bacteria such as Escherichia coli O157:H7, Salmonella typhimurium and Vibrio cholera O1 in seafood collected from natural sources and sold in retail may pose a serious threat to health if consumed. In this study, 18 razor clams (Solen spp.) samples were collected, all from vendors around the Kuching-Samarahan division. Bacteriological analysis, bacterial identification and biochemical tests were performed for all the isolates obtained from samples. Detection of virulence genes of E. coli O157:H7, S. typhimurium, and V. cholerae O1 were done through Polymerase Chain Reaction for isolates that showed positive results to biochemical tests. None of the isolates were detected positive for Escherichia coli O157:H7, Salmonella typhimurium and Vibrio cholera O1, indicating the absence of these three pathogenic organisms in samples of Solen spp. tested.